Responsible digital transformation in agri-food systems : a toolbox to practically address key identified challenges - Gardeazabal Monsalve, Andrea (CGIAR, 2023)
The dynamic digitalization of agri-food systems has generated a call for a Responsible Research and Innovation (RRI) approach, emphasizing ethical and sustainable technology adoption. Existing RRI frameworks prioritize fair benefits distribution, data privacy, and stakeholder engagement, aiming for transparent governance and proactive risk management. Despite these efforts, challenges persist in responsible digital innovation, including an excessive focus on technology design, inadequate stakeholder engagement, and difficulties in comprehending digital transformation processes. To address these challenges, this work introduces a comprehensive Responsible Digital Transformation Toolbox, tailored for practitioners and stakeholders in the agri-food systems domain. Based on a strategic framework classifying digital innovation challenges into Cyber, Social, and Physical dimensions, the toolbox focuses on three conditions for digital transformation: the design of digital technologies, access to these technologies, and navigating system complexity. By equipping practitioners with practical insights and tools, the aim is to facilitate a transformative shift towards sustainable, equitable, and responsible digital practices in the agri-food systems domain.